2023
DOI: 10.1093/ntr/ntad018
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Cessation and Prevention Interventions for Sexual and/or Gender Minority-Identified People and the Theories That Underpin Them: A Scoping Review

Abstract: Introduction This scoping review takes stock of the social and behavior change theories that have underpinned tobacco interventions tailored to sexual and/or gender minority (SGM) people and reflects on the need to target contextually-based drivers of SGM tobacco use inequities. Methods Data sources were Medline (Ovid), Scopus, PubMed, Google Scholar (01/01/1946 – 10/27/2022). Peer-reviewed publications in English from anywhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…While this study cannot determine the reason for cannabis use as a barrier to smoking cessation in SGM individuals, there are several potential reasons this may occur. For example, research in SGM populations highlight socioecological factors (e.g., depression symptoms, minority stress, tobacco norms) as contributors of tobacco use and cigarette cessation outcomes (McQuoid et al, 2023; Wheldon & Wiseman, 2021). It is possible that couse of cannabis and cigarettes may signify socioecological differences (e.g., greater depression symptoms, more frequent discrimination, greater coping motives; Buckner et al, 2023; Foster et al, 2016; Mattingly et al, 2023; McKelvey et al, 2021; Romm et al, 2022), which may serve as a barrier to smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this study cannot determine the reason for cannabis use as a barrier to smoking cessation in SGM individuals, there are several potential reasons this may occur. For example, research in SGM populations highlight socioecological factors (e.g., depression symptoms, minority stress, tobacco norms) as contributors of tobacco use and cigarette cessation outcomes (McQuoid et al, 2023; Wheldon & Wiseman, 2021). It is possible that couse of cannabis and cigarettes may signify socioecological differences (e.g., greater depression symptoms, more frequent discrimination, greater coping motives; Buckner et al, 2023; Foster et al, 2016; Mattingly et al, 2023; McKelvey et al, 2021; Romm et al, 2022), which may serve as a barrier to smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, gender minority individuals (i.e., transgender, nonbinary, genderqueer) have the highest tobacco and cannabis use prevalence among the California SGM population (Tan, 2022). These disparities between SGM and heterosexual/gender-conforming individuals are attributed to a variety of factors, including social norms around smoking and complex and interacting experiences of minority stressors (e.g., discrimination, family rejection) that can instill or amplify substance use (Lee et al, 2020; McQuoid et al, 2023; Wheldon & Wiseman, 2021). As cigarette and cannabis couse is prevalent in sexual minority and gender minority populations, a better understanding of how cannabis use impacts cigarette smoking during a cigarette quit attempt in SGM individuals is warranted to develop and test interventions.…”
mentioning
confidence: 99%
“…Resisting and coping with discrimination (Antin et al 2018, Budenz et al 2022, McCabe et al 2017, Sanders et al 2020b, economic and housing precarity (Gerend et al 2017, Wheldon & Wiseman 2019, mental health (Drescher et al 2018, Hinds et al 2022, industry targeting (Brock 2018, Emory et al 2019, and subcultural norms and aesthetics (Tinkler 2006, Youatt et al 2015 have been identified as important factors related to NT inequities in SGM populations. This growing body of research underscores the need for more SGM-inclusive and structurally-competent tobacco control efforts to better address persistent NT-related inequities (Antin et al 2023, Baskerville et al 2017, Hinds et al 2021, McQuoid et al 2023. A crucial step in this process requires an examination of how tobacco control strategies can lead to unintended consequences for certain groups more than others, and how those consequences might be mitigated (Antin et al 2015a, Bell & Dennis 2013, Evans-Polce et al 2015, Frohlich et al 2012, Graham 2012, Reuter 2013, Sanders et al 2020a, 2020b.…”
Section: Introductionmentioning
confidence: 99%

Trust in Tobacco Control

Sanders,
Annechino,
Lipperman-Kreda
et al. 2024
JCPH
“…Evidence-based interventions for smoking cessation reduce cigarette use, and several tailored interventions have been developed for Veterans 12 and LGB individuals. 13,14 For example, SmokefreeVET is a text messaging cessation program that provides Veterans with daily encouragement and advice, and strategies for coping with Veteran identified smoking triggers. 15,16 Vet Flexiquit is a web-based and text messaging program that uses an avatar who represents a supportive peer that shares their personal quitting journey.…”
mentioning
confidence: 99%